Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1175/jhm-d-15-0125.1
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Incoming Radiation below Forest Canopies: A Comparison of Different Radiometer Configurations

Abstract: Ground-based, subcanopy measurements of incoming shortwave and longwave radiation are frequently used to drive and validate energy balance and snowmelt models. These subcanopy measurements are frequently obtained using different configurations (linear or distributed; stationary or moving) of radiometer arrays that are installed to capture the spatial and temporal variability of longwave and shortwave radiation. Three different radiometer configurations (stationary distributed, stationary linear, and moving lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 32 publications
(53 reference statements)
2
30
0
2
Order By: Relevance
“…Similarly, forests affect ablation rates by diminishing turbulent heat fluxes and reducing incoming solar radiation (Table 1; Link et al, 2004;Link & Marks, 1999;Musselman et al, 2008Musselman et al, , 2015Veatch et al, 2009). Simultaneously, snow receives enhanced longwave radiation from the forest, which increases the melt rate, but the enhancement of longwave radiation has a more localized effect (Table 1) and varies between sun-lit and shaded forest edges (Lawler & Link, 2011;Musselman & Pomeroy, 2017;Seyednasrollah & Kumar, 2014;Webster et al, 2016Webster et al, , 2017Woo & Giesbrecht, 2000).…”
Section: Forest and Topographic Processes Affecting Snow Depth Variabmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, forests affect ablation rates by diminishing turbulent heat fluxes and reducing incoming solar radiation (Table 1; Link et al, 2004;Link & Marks, 1999;Musselman et al, 2008Musselman et al, , 2015Veatch et al, 2009). Simultaneously, snow receives enhanced longwave radiation from the forest, which increases the melt rate, but the enhancement of longwave radiation has a more localized effect (Table 1) and varies between sun-lit and shaded forest edges (Lawler & Link, 2011;Musselman & Pomeroy, 2017;Seyednasrollah & Kumar, 2014;Webster et al, 2016Webster et al, , 2017Woo & Giesbrecht, 2000).…”
Section: Forest and Topographic Processes Affecting Snow Depth Variabmentioning
confidence: 99%
“…Tuolumne had two sites classified as taiga (Dana Meadows and Dana Meadows South) and two sites classified as tundra, while sites at Jemez were all classified as warm forest. Warm forest was previously referred to as alpine in Sturm et al (1995) Golding and Swanson (1978), Lawler andLink (2011), Musselman et al (2015), and Seyednasrollah and Kumar (2014) Enhanced longwave radiation from the forest 1-2 m or 0.5 H Lawler and Link (2011), Musselman and Pomeroy (2017), Seyednasrollah and Kumar (2014), Webster et al (2016), and Woo and Giesbrecht (2000) Wind related deposition as a result of the forest 5-100 m or 3-10 H Brandle and Finch (1991), Hiemstra et al (2002Hiemstra et al ( , 2006, and Tabler (2003) 10.1029/2018WR022553…”
Section: Location and Datamentioning
confidence: 99%
“…Incoming shortwave and longwave radiation were measured simultaneously at 1 min (Alptal) and 15 s (Seehornwald) resolution. Details of the rail-mounted radiometers are described in StĂ€hli et al [2009] and Webster et al [2015] and were replicated when the equipment was moved from Alptal to the Seehornwald site in 2007. The subcanopy CNR1 moved along a 10 m heated rail at 10 min intervals at a constant velocity and at a height of approximately 2 m above the forest floor, covering a range of V f (Alptal: 0.09-0.18; Seehornwald; 0.02-0.05).…”
Section: Alptal and Seehornwaldmentioning
confidence: 99%
“…This process is called longwave enhancement and potentially contributes to ripening or melting of snow cover. Extensive observations of subcanopy longwave radiation in dense subalpine and alpine forests by Webster et al (2016a;2016b) revealed longwave enhancement values of up to 1.5, or 150%, and net longwave radiation fluxes into snow reaching 10-min averages of up to 40 W/m 2 during clear-sky days in spring. In contrast, net longwave radiation fluxes of about −100 W/m 2 are typical for snow under clear-sky conditions in unforested areas.…”
Section: Introductionmentioning
confidence: 99%